2020
DOI: 10.1177/1558944720964960
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hand Surgery Questions on Orthopedic In-training Examination From 2014 to 2019

Abstract: Background: The orthopedic in-training examination (OITE) continues to evolve over time. It is important for orthopedic residents and residency programs to have an up-to-date understanding of the content and resources being used on the OITE to study and tailor curricula accordingly. This study presents an updated analysis of the OITE hand domain from 2014 to 2019. Methods: All OITE questions related to hand surgery from 2014 to 2019 were analyzed for topic, subtopic, taxonomy, imaging modalities, and bibliomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Because of this emphasis, trends in recent examination questions have been investigated to aid in preparation for the annual examination. 17,[19][20][21][22][23][24][25][26] Although several studies have shown a correlation between OITE performance and passing the Part I Certifying Exam, the validity of the OITE as a predictive measure for success on the Certifying Exam has been questioned because the two examinations have been written by separate organizations without a common blueprint. [27][28][29][30][31] A linking study found that on the 2021 AAOS OITE, the minimum OITE score that corresponded to passing the Part I Certifying Exam was 69.2%, but this was noted to be applicable to the 2021 OITE examination only.…”
Section: Resident Evaluation Tools Orthopaedic In-training Examinationmentioning
confidence: 99%
“…Because of this emphasis, trends in recent examination questions have been investigated to aid in preparation for the annual examination. 17,[19][20][21][22][23][24][25][26] Although several studies have shown a correlation between OITE performance and passing the Part I Certifying Exam, the validity of the OITE as a predictive measure for success on the Certifying Exam has been questioned because the two examinations have been written by separate organizations without a common blueprint. [27][28][29][30][31] A linking study found that on the 2021 AAOS OITE, the minimum OITE score that corresponded to passing the Part I Certifying Exam was 69.2%, but this was noted to be applicable to the 2021 OITE examination only.…”
Section: Resident Evaluation Tools Orthopaedic In-training Examinationmentioning
confidence: 99%
“…7 Similarly, Lebrun et al found a statistically significant increase in T3 questions in the hand section from 2014 to 2019. 10 An increase in T3-level questions over time was also observed in the sports medicine 11,22 and oncology 17 sections of the OITE. As the rate of T3 questions is generally high and increasing in certain sections, the OITE is requiring an increasing level of clinical knowledge and critical thinking.…”
Section: Discussionmentioning
confidence: 86%
“…Most of these publications focus on identifying numbers of questions, types of questions, topics, references used, and publication lag. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This systematic review aims to assess all available studies that analyzed the types of questions in individual sections of the OITE. Currently, most relevant literature describes characteristics, references, and levels of evidence for individual sections of the examination.…”
mentioning
confidence: 99%
“…This methodology has been used in similar studies evaluating OITE questions after 2016. 1,6,10,20 The following data were abstracted for each question: topic, taxonomy, type of imaging used, and reference source with publication year. Shoulder and elbow question topics were adopted from a previous study 26 and included trauma, anatomy/biomechanics, degenerative joint disease/stiffness/arthroplasty, instability/athletic injury, rotator cuff, and miscellaneous.…”
Section: Methodsmentioning
confidence: 99%